Assessment of internal radiation exposure caused by radon in commercially bottled spring waters consumed in Turkey - Turhan, Şeref; Kurnaz, Aslı; Aydın, Erol (Informa UK Limited, 2023)
The variation of dissolved radon levels in water supplies remains of interest since radon ingested through drinking water can give considerable radiation to the lining of the stomach. This study aims to determine the radon concentration levels in bottled spring drinking water (BSW) brands commercially sold in Turkey using a radon gas monitor and to assess the internal radiation exposure caused by the ingestion and inhalation of radon. The activity concentrations of radon analyzed in 77 BSW brands varied from 7.1±0.8 to 28.7±2.7 mBq/L with an average of 15.7±5.1 mBq/L. The total annual effective dose was estimated to assess the radiological risk for three age groups in four different scenarios based on annual drinking water intake. All estimated dose values are well below the recommended reference dose of 100 µSv for drinking water. Therefore, radon gas in the investigated BSW samples poses no significant radiological risk to the public.
Keywords: Water Pollutants, Radioactive; Turkey; Radon; Radiation Monitoring; Drinking Water; Radiation Exposure; 13. Climate action; 6. Clean water